A comparative study on general product safety law between Malaysia and United Kingdom / Hamidah Che Seman …[et al.] - Che Seman, Hamidah; Mohammad Affandi, Huwaina; Hisham, Hidayah Hanim; Miar Ali, Zainab (2010)
This is a comparative study on product safety law between Malaysia and the United Kingdom. The main objective of the study is to compare the applicable law in Malaysia and the United Kingdom on general product safety. The main issue that will be focused is the law on product safety in term of the law that regulates the safety of the product including the standards of safety. Product recall will also be discussed, as recall is an important element to make sure the unsafe product is not distributed to the consumers. The United Kingdom is more advanced on product safety law as there is a specific provision under the General Product Safety Regulations 2005 which prohibits the producers from placing their products on market unless the products are safe. Furthermore, the procedures on recall product are more comprehensive while there is no such procedures in Malaysia which can be followed by the manufacturers. As a conclusion, there is still loop hole in the Malaysia law regarding product safety and the law needs to be added on to make clear provisions about the general standard of product safety.